2016
DOI: 10.3109/09513590.2015.1136617
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D on primary dysmenorrhea with vitamin D deficiency: a randomized double-blind controlled clinical trial

Abstract: Dysmenorrhea is common among women of reproductive age. This study aim was to investigate the effect of vitamin D (vit D) supplementation in treatment of primary dysmenorrhea with vit D deficiency. A randomized double-blind placebo-controlled clinical trial was conducted on 60 women with primary dysmenorrhea and vit D deficiency referred to our clinic at Arash Women's Hospital from September 2013 to December 2014. Eligible women were randomly assigned into treatment and control groups (30 in each group). Indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 16 publications
1
40
0
8
Order By: Relevance
“…Women with primary dysmenorrhea who use non-steroidal anti-inflammatory drugs are suggested to use natural antioxidants such as vitamin E, vitamin C, and β-carotenoids for the reduction of pain [7,53]. Single randomized controlled trials showed the effect of vitamin supplements on the reduction of menstrual pain reduction [63,66,67], but a Cochrane meta-analysis on the effect of dietary supplements for primary dysmenorrhea lacked high quality evidence to support the effectiveness and safety of any dietary supplement for dysmenorrhea. Therefore, more research with higher methodological qualities are required [24].…”
Section: Discussionmentioning
confidence: 99%
“…Women with primary dysmenorrhea who use non-steroidal anti-inflammatory drugs are suggested to use natural antioxidants such as vitamin E, vitamin C, and β-carotenoids for the reduction of pain [7,53]. Single randomized controlled trials showed the effect of vitamin supplements on the reduction of menstrual pain reduction [63,66,67], but a Cochrane meta-analysis on the effect of dietary supplements for primary dysmenorrhea lacked high quality evidence to support the effectiveness and safety of any dietary supplement for dysmenorrhea. Therefore, more research with higher methodological qualities are required [24].…”
Section: Discussionmentioning
confidence: 99%
“…(2016) tarafından yapılan bir diğer randomize kontrollü klinik çalışmada PD'li hastalara 8 hafta süreyle (50,000 IU/hafta) vitamin D desteği uygulanmış ve plasebo kontrol grubuna kıyasla hasta grubunda vitamin D düzeyleri yüksek bulunmakla (p<0,001) birlikte uygulama sonunda ve hatta uygulamadan bir ay sonra bile ağrı şiddetle-rinin düştüğü (p<0,001) rapor edilmiştir. 9 Ayrıca, ülkemizde yakın dönemde yapılan bir araştırmada 18-25 yaş arası PD'li kadınların kontrole kıyasla serum vitamin D düzeylerinin belirgin düşük (p=0,001), ağrı şiddetinin değerlendirildiği görsel analog ölçeği (VAS) skorlarının ise yüksek (p=0,001) bulunduğu, VAS skorları ile vitamin D düzeyleri arasında da zıt yönlü istatistiksel açıdan anlamlı bir ilişki (r=-0,713, p=0,001) bulunduğu bildirilmiştir. 10 Mevcut veriler ışığında vitamin D'nin özellikle ağrı kontrolü başta olmak üzere çeşitli PD semptomları üzerinde önemli etkileri olabileceği düşünülmektedir.…”
Section: Vi̇tami̇n D Ve Pri̇mer Di̇smenoreunclassified
“…According to some studies, the severity of manifestations were significantly decreased if high-dose cholecalciferol was prescribed [17,18].…”
Section: The Role Of Vitamin D In the Development Of Menstrual Functionmentioning
confidence: 99%
“…According to some studies, the role of vitamin D deficiency in the development of menstrual disorders in women was considered to be proven; therefore, in these disorders, high-dose vitamin D had to be administered [2]. However, according to other authors, the level of vitamin D (in combination with calcium) was of no clinical significance and a positive correlation with the function of the reproductive organs was not found [3].…”
Section: Introductionmentioning
confidence: 99%